2016
DOI: 10.1016/j.dental.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of methacrylate-based composites containing thio-urethane oligomers

Abstract: Objective To evaluate the ability of thio-urethane oligomers to improve the properties of restorative composite resins. Materials and methods Oligomers were synthesized by combining 1,6-hexanediol-diissocyante (aliphatic) with pentaerythritol tetra-3-mercaptopropionate (PETMP) or 1,3-bis(1-isocyanato-1-methylethyl)benzene (aromatic) with trimethylol-tris-3-mercaptopropionate (TMP), at 1:2 isocyanate:thiol, leaving pendant thiols. Oligomers were added at 0–20 wt% to BisGMA-TEGDMA (70–30 wt%). Silanated inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
1
26
3
Order By: Relevance
“…In this study, the conversion of specimens of similar thickness polymerized with similar irradiance and final dose was followed separately, and the time to reach the crossover between storage and loss modulus in shear was used to estimate the conversion at which the crossover took place. The chain-transfer reactions from the pendant thiols on the thio-urethane backbone to the surrounding methacrylate matrix delayed gelation (G’/G”) to a higher degree of conversion in all TU-based materials (more markedly for PETMP-AL and PETMP-AR, the highest among the oligomer groups), avoiding early-stage diffusion limitations to polymerization, delaying stress development [30, 31], and ultimately reducing overall polymerization stress [16, 32]. In addition, the final shear storage modulus obtained from rheometer has shown a significant increase in cements composed by selected groups of oligomers (except for PETMP-AL and PETMP-CC).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the conversion of specimens of similar thickness polymerized with similar irradiance and final dose was followed separately, and the time to reach the crossover between storage and loss modulus in shear was used to estimate the conversion at which the crossover took place. The chain-transfer reactions from the pendant thiols on the thio-urethane backbone to the surrounding methacrylate matrix delayed gelation (G’/G”) to a higher degree of conversion in all TU-based materials (more markedly for PETMP-AL and PETMP-AR, the highest among the oligomer groups), avoiding early-stage diffusion limitations to polymerization, delaying stress development [30, 31], and ultimately reducing overall polymerization stress [16, 32]. In addition, the final shear storage modulus obtained from rheometer has shown a significant increase in cements composed by selected groups of oligomers (except for PETMP-AL and PETMP-CC).…”
Section: Discussionmentioning
confidence: 99%
“…Bars having the same dimensions as the 3D printed samples (25 × 2 × 2 mm) were fabricated by dispensing the materials in a silicon mold covered with a glass slide on top and bottom, and allowing the materials to cure following the manufacturer’s recommendations. Samples were then stored at ambient temperature for 24 hours, had their respective length, width and thickness measured, and the mechanical properties were determined using 3-point bending method, as previously described 21 . The elastic modulus was determined from the slope of the initial linear part of the load-deformation curve according to the ISO 4049 standard.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies have demonstrated that this is not always the case [5,10]. In this context, thiourethane oligomers have been proposed as an alternative stress reducing additive, allying the higher molecular weight of the oligomer with thiol chemistry, which affords lower stress through delayed gelation and vitrification [1619]. The rationale is that the thiol functional groups work as chain transfer agents to promote a radically assisted step-growth polymerization of methacrylates [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, thiourethane oligomers have been proposed as an alternative stress reducing additive, allying the higher molecular weight of the oligomer with thiol chemistry, which affords lower stress through delayed gelation and vitrification [1619]. The rationale is that the thiol functional groups work as chain transfer agents to promote a radically assisted step-growth polymerization of methacrylates [18,19]. In fact, several prior studies demonstrated the effectiveness of the addition of thiourethane oligomers on polymerization stress reduction and depth of polymerization increase, which in turn relates to the high refractive index of these oligomers [2023].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation